2019
DOI: 10.1073/pnas.1818523116
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal atrophy and intrinsic brain network dysfunction relate to alterations in mind wandering in neurodegeneration

Abstract: Mind wandering represents the human capacity for internally focused thought and relies upon the brain’s default network and its interactions with attentional networks. Studies have characterized mind wandering in healthy people, yet there is limited understanding of how this capacity is affected in clinical populations. This paper used a validated thought-sampling task to probe mind wandering capacity in two neurodegenerative disorders: behavioral variant frontotemporal dementia [(bvFTD); n = 35] and Alzheimer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 58 publications
5
55
1
Order By: Relevance
“…The Level x Group interaction was significant [F(6,300) = 3.06, p < 0.01]. We followed this interaction with tests of simple effects to determine whether the groups differed in their response frequencies at any Level apart from Level 4, which we showed in our Figure S1 for analyses and results), replicating previous studies using the task (Geffen et al, 2017;O'Callaghan et al, 2019).…”
Section: Hallucinators Had a Higher Frequency Of Mind-wandering Compasupporting
confidence: 62%
See 1 more Smart Citation
“…The Level x Group interaction was significant [F(6,300) = 3.06, p < 0.01]. We followed this interaction with tests of simple effects to determine whether the groups differed in their response frequencies at any Level apart from Level 4, which we showed in our Figure S1 for analyses and results), replicating previous studies using the task (Geffen et al, 2017;O'Callaghan et al, 2019).…”
Section: Hallucinators Had a Higher Frequency Of Mind-wandering Compasupporting
confidence: 62%
“…Our generic course seen in ageing (Maillet and Schacter, 2016) and exacerbated in several neurodegenerative diseases (Geffen et al, 2017;Gyurkovics et al, 2018;O'Callaghan et al, 2019).…”
Section: Follow-up Seed-to-voxel Functional Connectivity With a Primamentioning
confidence: 99%
“…At the core of this distributed large-scale network 75 , the posterior cingulate cortex and its connectivity with regions supporting cognitive control [76][77][78] and regions supporting episodic knowledge [79][80][81] are thought to orchestrate the ongoings of spontaneous thought 2 . Indeed, a recent study in a clinical population showed a correlation between the integrity of this connectivity and mindwandering capacity 82 . Further, a diffuse increase in theta activity was recorded during mindwandering as compared to a breath focus task 45 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, dementia that results in atrophy to the posterior cingulate cortex impacts upon the intensity of mind-wandering episodes 21 and our study highlights the connectivity of this region as important for patterns of mental time travel with vivid detail. Our study, therefore, builds on prior work that uses lesion based methods by showing that in a young healthy population individuals who perform better on task reliant on semantic processes, tend to report more detailed mental time travel.…”
Section: Resultsmentioning
confidence: 58%
“…In healthy participants, for example, changes in activity within the default mode network are linked to patterns of experience with rich subjective details in both episodic memory and working memory tasks contexts. In patients with forms of dementia that target elements of the default mode network (including posterior cingulate cortex), patterns of off-task experience are less intense 21 and scene construction is impaired, particularly global features of the experience 22 . Likewise, patients with semantic dementia, in which atrophy is focussed on the anterior temporal lobes, have deficits in the ability to imagine the future 23 .…”
Section: Introductionmentioning
confidence: 99%